Human sterilization surgery and Argentinian law: biomedical, legal and ethical aspects - Cecchetto, Sergio; Urbandt, Patricia; Bostiancic, María Carla (Acta Bioethica, 2007)
Argentine's congress recently dictated the 26.130-2006 law about the procedure for sterilization surgery interventions in men and women. This work offers a review of the legal situation in Argentine and in the world. It points out critical observations to its items, highlighting the right to access to other non surgical contraceptive methods; the advisability for the interested sexual partner to know which decision was taken; the need to determine the competence of candidates prior to surgical intervention stated by an interdisciplinary professional team; the duty to regulate the special situation of legally incompetent persons; the importance of establishing an adequate time between the information and the patient's consent; to prevent sterilization to become the only medical practice paid by the public health system, social security organizations and prepaid medical entities; and to be careful about the reach and nature of conscientious objection in each specific circumstance.